RETRACTED ARTICLE: The complete mitochondrial genome of the tobacco budworm, Helicoverpa assulta. (1st November 2016) - Li, Zhao-Qun; Zhang, Shuai; Luo, Jun-Yu; Cui, Jin-Jie; Dong, Shuang-Lin
Abstract: The complete mitochondrial genome of the tobacco budworm Helicoverpa assulta was sequenced. It is 15, 351 bp in length, and contains 22 transfer RNA genes, 13 protein-coding genes (PCGs), 2 rRNA genes and a non-coding AT-rich region. The H. assulta mitogenome displays a very high level of identity (99.76%) with Helicoverpa armigera . The genome base composition is 40.50% A, 40.40% T, 11.32% C and 7.70% G. Similar to other Lepidoptera insects, all PCGs are initiated by a typical ATN codon, except CO1, which starts with CGA. Nine PCGs have the standard, complete stop codon (TAA), and the other four PCGs end with the incomplete stop codon TA–.